The logic of the spirit : human development in theological perspective - Loder, James E. (James Edwin) (San Francisco Jossey-Bass, cop., 1998)
This work demonstrates how a theological perspective enlarges and deepens our understanding of how humans grow and develop from birth to healthy adulthood. The author brings preeminent psychological models of human development into conversation with seminal Christian theological perspectives.
Keywords: Christianity -- Psychology. Developmental psychology -- Religious aspects -- Christianity